Bubble Electrospinning and Bubble-Spun Nanofibers - Wan, Lynn Y. (Recent Patents on Nanotechnology, 2020)
Electrospinning is a highly efficient technology for fabrication of a wide variety of polymeric nanofibers. However, the development of traditional needle-based electrospinning has been hampered by its low productivity and need of tedious work dealing with needles cleaning, installation and uninstallation. As one of the most promising needleless electrospinning means, bubble electrospinning is known for its advantages of high productivity and relatively low energy consumption due to the introduction of a third force, air flow, as a major force overcoming the surface tension. In this paper, the restrictions of conventional electrospinning and the advantages of needleless electrospinning, especially the bubble electrospinning were elaborated. Reports and patents on bubble-spun nanofibers with unique surface morphologies were also reviewed in respect of their potential applications.
Keywords: morphology